Współczesne rynki pracy - wybrane problemy - Kubiczek, Agata (Present labour markets - selected problems, 2006)
The problems ofthe labour market, and especially the problems ofthe unemployment, for a long time have attracted attention of theoreticians and economic politicians. It is known that the unemployment is a normal phenomenon, occuring in every system of the market economy. The twentieth century and the turn of the twenty-first century will certainly enter the history ofthe world not only with splendid technical and scientific successes, but also with the mass unemployment, with the growing poverty. This article shows basic sources of serious problems on the labour market in the time of the globalization. Part one discusses directions of changes on the labour market, mostly in relation to the economic structure, consequently in relation to the structure of employment, and the what role foreign investments play in these transformations. Then the author attempts to find the answer to the question whether in the time of the globalization the full employment will be possible to achieve. Generally, the reduction of the total unemployment will be able thanks to international programmes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 269-278